A Continuous-Flow Model for in vitro Cultivation of Mixed Microbial Populations Associated With Cystic Fibrosis Airway Infections - O’Brien, Thomas James; Welch, Martin (Frontiers in Microbiology, 2019)
The airways of people with cystic fibrosis (CF) provide a nutrient-rich environment which favours colonization by a variety of bacteria and fungi. Although the dominant pathogen associated with CF airway infections is Pseudomonas aeruginosa, it is becoming increasingly clear that inter-species interactions between P. aeruginosa and other colonists in the airways may have a large impact on microbial physiology and virulence. However, there are currently no suitable experimental models that permit long-term co-culture of P. aeruginosa with other CF-associated pathogens. Here, we redress this problem by describing a “3R’s-compliant” continuous-flow in vitro culture model which enables long-term co-culture of three representative CF-associated microbes: P. aeruginosa, Staphylococcus aureus and Candida albicans. Although these species rapid out-compete one another when grown together or in pairs in batch culture, we show that in a continuously-fed setup, they can be maintained in a very stable, steady-state community. We use our system to show that even numerically (0.1%) minor species can have a major impact on intercellular signaling by P. aeruginosa. Importantly, we also show that co-culturing does not appear to influence species mutation rates, further reinforcing the notion that the system favours stability rather than divergence. The model is experimentally tractable and offers an inexpensive yet robust means of investigating inter-species interactions between CF pathogens.